Body composition and body mass index are independently associated with widespread pain and experimental pain sensitivity in older adults: a pilot investigation - Johnson, Alisa J.; Peterson, Jessica A.; Vincent, Heather K.; Manini, Todd; Cruz-Almeida, Yenisel (Frontiers in Pain Research, 2024)
IntroductionChronic musculoskeletal (MSK) pain is prevalent in older adults and confers significant risk for loss of independence and low quality of life. While obesity is considered a risk factor for developing chronic MSK pain, both high and low body mass index (BMI) have been associated with greater pain reporting in older adults. Measures of body composition that distinguish between fat mass and lean mass may help to clarify the seemingly contradictory associations between BMI and MSK pain in this at-risk group.MethodsTwenty-four older adults (mean age: 78.08 ± 5.1 years) completed dual-energy x-ray absorptiometry (DEXA), and pain measures (Graded Chronic Pain Scale, number of anatomical pain sites, pressure pain threshold, mechanical temporal summation). Pearson correlations and multiple liner regression examined associations between body mass index (BMI), body composition indices, and pain.ResultsSignificant positive associations were found between number of pain sites and BMI (b = 0.37) and total fat mass (b = 0.42), accounting for age and sex. Total body lean mass was associated with pressure pain sensitivity (b = 0.65), suggesting greater lean mass is associated with less mechanical pain sensitivity.DiscussionThe results from this exploratory pilot study indicate lean mass may provide additional resilience to maladaptive changes in pain processing in older adults, and highlights the importance of distinguishing body composition indices from overall body mass index to better understand the complex relationship between obesity and MSK pain in older adults.